Bottle and newspaper make young tree happy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
If you have experience with planting young trees, you will know that the best time for planting is a few weeks before the rainy season starts. Young trees usually develop deeper root systems if the soil is relatively dry and the water table is low....